The Efficacy of Entomopathogenic Nematodes Plus an Adjuvant against Helicoverpa zea and Chrysodeixis includens in Aboveground Applications - Zhang Minling; Spaulding Nathan; Reddy Gadi V.P.; Shapiro-Ilan David I (Journal of Nematology, 2024)
In the southern United States, corn earworm, Helicoverpa zea (Boddie), and soybean looper, Chrysodeixis includens (Walker) are economically important crop pests. Although Bt crops initially provided effective control of target pests such as H. zea, many insect pests have developed resistance to these Bt crops. Alternative approaches are needed, including biological control agents such as entomopathogenic nematodes (EPNs). However, the effectiveness of EPNs for aboveground applications can be limited due to issues such as desiccation and ultraviolet radiation. Effective adjuvants are needed to overcome these problems. Ten strains of EPNs were tested for virulence against eggs, first to fourth instars, fifth instars, and pupae of H. zea and C. includens in the laboratory. These 10 EPN strains were Heterorhabditis bacteriophora (HP88 and VS strains), H. floridensis (K22 strain), Hgkesha (Kesha strain), Steinernema carpocapsae (All and Cxrd strains), S. feltiae (SN strain), S. rarum (17c+e strain), and S. riobrave (355 and 7–12 strains). EPNs could infect eggs of H. zea or C. includens in the laboratory, but the infection was low. The mortality caused by 10 EPN strains in seven days was significantly higher for the first to fourth instars of H. zea compared to the control, as was the fifth instars of H. zea. Similarly, for the first to fourth and fifth instars of C. includens, the mortality was significantly higher compared to the controls, respectively. However, only S. riobrave (355) had significantly higher mortality than the control for the pupae of H. zea. For the pupae of C. includens, except for H. bacteriophora (HP88), S. rarum (17c+e), and H. floridensis (K22), the mortality of the other seven strains was significantly higher than the control. Subsequently, S. carpocapsae (All) and S. riobrave (7–12) were chosen for efficacy testing in the field with an adjuvant 0.066% Southern Ag Surfactant (SAg Surfactant).